IMPLEMENTATION OF EXPOSITORY LEARNING TO INCREASE THEMATIC LEARNING RESULTS THEME 1 MYSELF SUB THEME 1 ME AND A NEW FRIEND IN THE THEMATIC LESSON IN CLASS I MIN 3 CIJANTUNG IN 2018/2019 - Siti Mahmudah (Indonesian Journal of Multidisciplinary Science, 2022)
The problems to be studied in this study are: (a) Does expository affect thematic learning outcomes for Class I students? (b) How is the influence of the expository on the mastery of thematic material in Grade I students? Meanwhile, the objectives of this research are: (a) To reveal the effect of expository on thematic learning outcomes in Grade I students. (b) To reveal the effect of expository learning on mastery of thematic material in Grade I students. This study usesaction researchas much as three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the students of Class I SD Negeri. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (67%), cycle II (75%), cycle III (92%). The conclusion of this research is the application of expository can have a positive effect on the achievement and learning motivation of Class I students and this learning model can be used as an alternative thematic learning.